Curable resin composition, dry film, cured product, and printed circuit board

KR103030358B1Active Publication Date: 2026-10-13TAIYO INK MFG CO KOREALTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020240033396
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-08
Publication Date
2026-10-13
Estimated Expiration
2044-03-08

Smart Images

  • Figure 112024026668154-PAT00005_ABST
    Figure 112024026668154-PAT00005_ABST
Patent Text Reader

Abstract

One embodiment of the present invention relates to a curable resin composition comprising (A) a curable resin, (B) a white inorganic filler, (C) a first extender pigment, (D) a second extender pigment, and (E) a photoinitiator, wherein the average particle size of the first extender pigment is larger than the average particle size of the second extender pigment, and the content of the first extender pigment is 25% by weight or less based on the total weight of the resin composition. Such a curable resin composition may exhibit excellent reflectivity, discoloration stability, crack characteristics, gloss, anti-mura effect, and / or leveling.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a curable resin composition, a dry film, a cured product, and a printed circuit board. More specifically, the dry film comprises a resin layer formed by a dry film of the curable resin composition formed on a support film, the cured product is obtained by curing the resin layer of the dry film, and the printed circuit board comprises the cured product. Background Technology

[0002] A printed circuit board is generally formed by etching copper foil along circuit lines against a laminated board, on which electronic components are placed in designated locations and soldered. A solder resist film is used as a protective layer for the circuit when soldering electronic components to such a printed circuit board. During soldering, the solder resist film prevents solder from adhering to unnecessary areas and also prevents circuit conductors from being directly exposed to air and corroded by oxygen or moisture. Furthermore, it functions as a permanent protective layer for the circuit board. Therefore, various properties such as adhesion, electrical insulation, solder heat resistance, solvent resistance, and chemical resistance are required.

[0003] Furthermore, printed circuit boards are following a path of miniaturization, multilayering, and single-board integration to achieve high density, and mounting methods are also shifting toward Surface Mount Technology (SMT). Consequently, there is an increasing demand for solder resist films that are finer, have higher resolution, higher precision, and higher reliability.

[0004] As a technology for forming such solder resist patterns, photoresist methods capable of accurately forming fine patterns are being used; among them, alkali-developed liquid photoresist methods are becoming the mainstream, particularly due to considerations regarding the environment.

[0005] Meanwhile, in recent years, there has been an increasing number of applications in which light-emitting diodes (LEDs) that emit light with low power are directly mounted on printed circuit boards coated with a solder resist film, such as backlights for liquid crystal displays in mobile terminals, personal computers, and televisions, as well as light sources for lighting fixtures. Therefore, in order to efficiently utilize the light from LEDs, printed circuit boards having a low-gloss, high-reflectivity solder resist film are required.

[0006] In particular, the reflectance of the solder resist on direct-lit backlight unit (BLU) substrates was an important factor, as too high a reflectance results in the LED chip area being bright and the surrounding area being dark, while too low a reflectance results in the opposite phenomenon.

[0007] However, conventionally, even if the solder resist is matte to achieve low gloss, optical properties such as reduced reflectivity or discoloration stability are poor, making it difficult to exhibit both low gloss and high reflectivity characteristics. This required additional processes or the application of additional layers, and it was difficult to apply to backlight units.

[0008] In addition, when implementing a surface light source by arranging multiple point light source LED chips, there were problems such as the occurrence of a mura phenomenon when the distance between chips was large.

[0009] Accordingly, there is a demand for the manufacture of a solder resist that exhibits low gloss and excellent discoloration stability and reflectance characteristics through a simple process, without the need for additional processes or the addition of separate sheets or films. Prior art literature

[0010] Korean Registered Patent No. 10-1610822 The problem to be solved

[0011] The present invention provides a technology for a curable resin composition capable of producing a white solder resist that exhibits low gloss, excellent discoloration stability, and reflectance characteristics through a simple process without the addition of a separate sheet or film.

[0012] In addition, the present invention is intended to provide a dry film, a cured product, and a printed circuit board using the above-mentioned curable resin composition. means of solving the problem

[0013] One embodiment of the present invention relates to a curable resin composition.

[0014] In one aspect, the curable resin composition comprises (A) a curable resin, (B) a white inorganic filler, (C) a first extender pigment, (D) a second extender pigment, and (E) a photoinitiator, wherein the average particle size of the first extender pigment is larger than the average particle size of the second extender pigment, and the content of the first extender pigment may be 25% by weight or less based on the total weight of the resin composition.

[0015] In one aspect, the white inorganic filler (B) may be titanium oxide, zinc oxide, basic carbonate, basic sulfate, sulfate, zinc sulfide, antimony oxide, aluminum hydroxide, silica, barium sulfate, or a combination thereof.

[0016] In one aspect, the first extender pigment and the second extender pigment may be independently selected from talc, barium sulfate (BaSO4), silica, and calcium carbonate (CaCO3).

[0017] In one aspect, the average particle size of the first extender pigment and the second extender pigment may be 1 to 13 μm.

[0018] In one aspect, the average particle size of the first sieving pigment may be 3 to 13 μm.

[0019] In one aspect, the average particle size of the second sieving pigment may be 1 to 4 μm.

[0020] In one aspect, the content of the first extender pigment may be greater than the content of the second extender pigment.

[0021] In one aspect, based on the total weight of the resin composition, the content of the second extender pigment may be 6% by weight or less.

[0022] In one aspect, based on the total weight of the resin composition, the sum of the content of the first extender pigment and the second extender pigment may be 3% by weight or more.

[0023] In one aspect, the curable resin composition may be for forming a solder resist.

[0024] Another embodiment of the present invention relates to a dry film comprising a support film and a resin layer formed on the support film, the resin layer being a dried film of the above-described curable resin composition.

[0025] Another embodiment of the present invention relates to a cured product obtained by curing a resin layer of the dry film described above.

[0026] In one aspect, the cured material may have an average surface roughness (Ra) of 0.2 or higher.

[0027] Another embodiment of the present invention relates to a cured product obtained by curing the above-described curable resin composition.

[0028] In one aspect, the cured material may have an average surface roughness (Ra) of 0.2 or higher.

[0029] Another embodiment of the present invention relates to a printed circuit board comprising the cured material described above. Effects of the invention

[0030] By including two types of extender pigments with different particle sizes in a specific amount according to one embodiment of the present invention, sufficient reliability regarding characteristics such as discoloration stability and reflectance can be secured without a separate reflective sheet or light-diffusing sheet.

[0031] For example, a curable resin composition according to one aspect of the present invention comprises (A) a curable resin, (B) a white inorganic filler, (C) a first extender pigment, and (D) a second extender pigment, wherein the average particle size of the first extender pigment is larger than the average particle size of the second extender pigment, and the content of the first extender pigment is 25% by weight or less based on the total weight of the resin composition, so as to exhibit excellent reflectivity, discoloration stability, crack characteristics, gloss, anti-mura effect, and / or leveling.

[0032] Due to these characteristics, the solder resist produced by the curable resin composition of the present invention can exhibit excellent effects.

[0033] In addition, the present invention can provide a dry film, a cured product, and a printed circuit board using the above-mentioned curable resin composition. Brief explanation of the drawing

[0034] Figure 1 relates to the mura evaluation criteria used in the present invention. Specific details for implementing the invention

[0035] Various embodiments of the present invention are described below.

[0036] [Curable resin composition]

[0037] One embodiment of the present invention relates to a curable resin composition comprising (A) a curable resin, (B) a white inorganic filler, (C) a first extender pigment, and (D) a second extender pigment.

[0038] Another embodiment of the present invention relates to a curable resin composition comprising (A) a curable resin, (B) a white inorganic filler, (C) a first extender pigment, (D) a second extender pigment, and (E) a photoinitiator.

[0039] In one aspect, the average particle size of the first extender pigment is larger than the average particle size of the second extender pigment, and the content of the first extender pigment may be 25% by weight or less based on the total weight of the resin composition.

[0040] The above curable resin composition can exhibit excellent reflectivity, discoloration stability, crack characteristics, gloss, anti-mura effect, and leveling.

[0041] For example, the above-mentioned curable resin composition may be a curable resin solder resist composition for curing to form a solder resist.

[0042] Below, each component of the curable resin composition is described in detail.

[0043] [(A) Curable Resin]

[0044] Examples of curable resins include photocurable resins that contribute to a photocuring reaction upon light irradiation, thermosetting resins that contribute to a thermosetting reaction upon heating, and photocurable thermosetting resins that contribute to either reaction. The curable resin composition may contain only one of the thermosetting resin and the photocurable resin, or may contain both.

[0045] As for the photocurable resin, it is sufficient to be a resin that exhibits electrical insulation properties when cured by irradiation with active energy rays, and for example, in the present disclosure, it may be a compound having one or more ethylenically unsaturated bonds in its molecule. By including a photocurable resin, the strength of the cured film can be improved. The photocurable resin may be used as a single type or in combination of two or more types.

[0046] Compounds having ethylenically unsaturated bonds, such as known and commonly used photopolymerizable oligomers and photopolymerizable monomers, can be used. Among these, it is preferable to use photopolymerizable monomers in that they can further impart crosslinkability or curability to the cured film.

[0047] Photopolymerizable oligomers are oligomers having an ethylenically unsaturated double bond. Examples of photopolymerizable oligomers include unsaturated polyester-based oligomers and (meth)acrylate-based oligomers. Examples of (meth)acrylate-based oligomers include epoxy(meth)acrylates such as phenol novolak epoxy(meth)acrylate, cresol novolak epoxy(meth)acrylate, and bisphenol-type epoxy(meth)acrylate; urethane(meth)acrylates; epoxyurethane(meth)acrylates; polyester(meth)acrylates; polyether(meth)acrylates; and polybutadiene-modified(meth)acrylates.

[0048] Photopolymerizable monomers are monomers having ethylenically unsaturated double bonds.Examples of such photopolymerizable monomers include, for instance, styrene derivatives such as styrene, chlorostyrene, and α-methylstyrene; vinyl esters such as vinyl acetate, vinyl butyrate, or vinyl benzoate; vinyl ethers such as vinyl isobutyl ether, vinyl-n-butyl ether, vinyl-t-butyl ether, vinyl-n-amyl ether, vinyl isoamyl ether, vinyl-n-octadecyl ether, vinylcyclohexyl ether, ethylene glycol monobutylvinyl ether, and triethylene glycol monomethylvinyl ether; and (meth)acrylamides such as acrylamide, methacrylamide, N-hydroxymethylacrylamide, N-hydroxymethylmethacrylamide, N-methoxymethylacrylamide, N-ethoxymethylacrylamide, and N-butoxymethylacrylamide. Allyl compounds such as trialyl isocyanurate, diallyl phthalate, and diallyl isophthalate; alkyl (meth)acrylates such as 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and cyclohexyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and pentaerythritol tri(meth)acrylate); mono or di(meth)acrylates of alkylene oxide derivatives such as ethylene glycol, propylene glycol, diethylene glycol, and dipropylene glycol; Examples include polyhydric alcohols such as hexanediol, trimethylolpropane, pentaerythritol, ditrimethylolpropane, dipentaerythritol, and trihydroxyethyl isocyanulate, or polyhydric (meth)acrylates of their ethylene oxide or propylene oxide adducts; (meth)acrylates of phenols such as phenoxyethyl (meth)acrylate and polyethoxydi(meth)acrylate of bisphenol A, or ethylene oxide or propylene oxide adducts; (meth)acrylates of glycidyl ethers such as glycerin diglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanulate; and melamine (meth)acrylate.One type of photopolymerizable monomer may be used alone, or two or more types may be used in combination.

[0049] Photocurable resins can be represented by, for example, the following chemical formula (1), but are not limited thereto.

[0050] <Chemical Formula (1)>

[0051]

[0052] In the above chemical formula (1), X are independently C1-C 10 It is an alkyl group or a hydrogen atom, and R is C1-C 10 alkyl group or C1-C 10 It is a hydroxyalkyl group.

[0053] As the thermosetting resin, any known type may be used. By including a thermosetting resin in the curable resin composition, the heat resistance of the cured film can be improved. Examples of thermosetting resins include known and commonly used types such as epoxy resin, isocyanate compound, block isocyanate compound, amino resin, polyfunctional oxetane compound, benzoxazine resin, carbodiimide resin, cyclocarbonate compound, and episulfide resin. Among these, the preferred thermosetting resin is epoxy resin. The thermosetting resin may be used as a single type or in combination of two or more types.

[0054] The epoxy resin of the present invention may use a known conventional compound having one or more epoxy groups. For example, it may be a compound having two or more epoxy groups. For example, it may be a monoepoxy compound such as butylglycidyl ether, phenylglycidyl ether, glycidyl (meth)acrylate, etc., a bisphenol A type epoxy resin, bisphenol S type epoxy resin, bisphenol F type epoxy resin, phenol novolak type epoxy resin, cresol novolak type epoxy resin, aliphatic ring epoxy resin, trimethylolpropane polyglycidyl ether, phenyl-1,3-diglycidyl ether, biphenyl-4,4'-diglycidyl ether, 1,6-hexanediol diglycidyl ether, diglycidyl ether of ethylene glycol or propylene glycol, sorbitol polyglycidyl ether, tris(2,3-epoxypropyl)isocyanurate, triglycidyl tris(2-hydroxyethyl)isocyanurate, etc., having two or more epoxy groups in one molecule. These can be used individually or in combination of two or more types depending on the required characteristics.

[0055] In the curable resin composition of the present invention, the content of (A) the curable resin may be 15 to 55 weight%, 20 to 50 weight%, or 25 to 50 weight% with respect to the total composition. The composition comprises a solid and a solvent. The content of (A) the curable resin may be calculated based on the solid content conversion.

[0056] (A) If the content of the curable resin is within the above range, excellent yellowing resistance and high reflectivity can be achieved, a solder resist film can be formed well, excellent pencil hardness and adhesion can be exhibited, and the tack-free drying properties of the film and the reduction of undercut can be suppressed.

[0057] [(B) White inorganic filler]

[0058] A curable resin composition according to one embodiment of the present invention can obtain a high reflectance by including a white inorganic filler.

[0059] Examples of white inorganic fillers include titanium oxide, zinc oxide, basic carbonates, basic sulfates, sulfates, zinc sulfide, antimony oxide, aluminum hydroxide, silica, barium sulfate, etc. For example, when a composition is formed using a mixture of barium sulfate and silica as a white inorganic filler, the L value is 80 or higher, the a value is -5 or higher, and the b value is -5 or higher. The above L value may be measured according to Hunter 1948. For example, when a composition is formed using a high content of titanium oxide and silica as a white inorganic filler, the L value is 90 or higher, the a value is -3 or higher, and the b value is -3 or higher, resulting in high whiteness and reflectance. For example, when a composition is formed using titanium oxide as an inorganic filler, the L value is 95 or higher, the a value is -2 or higher, and the b value is -1 or higher, resulting in the highest whiteness and reflectance.

[0060] For example, the method for manufacturing titanium oxide may be either the sulfuric acid method or the chlorine method, and for example, it may be the chlorine method. For example, sulfuric acid may not be used in the manufacturing process. In addition, the surface treatment of titanium oxide is not particularly limited, but it may be titanium oxide treated with an acid other than sulfuric acid, such as hydrochloric acid, nitric acid, phosphoric acid, or acetic acid, during neutralization.

[0061] As for the titanium oxide, any structure of titanium oxide among rutile, anatase, and rams-delight types may be used, and one type may be used alone or two or more types may be used in combination. Among these, rams-delight type titanium oxide is rams-delight type Li 0.5 It can be obtained by performing a lithium TiO2 chemical oxide removal treatment.

[0062] Among the above, using rutile-type titanium oxide can further improve heat resistance, make it difficult to cause discoloration due to light irradiation, and make it difficult to degrade quality even in strict usage environments. In particular, heat resistance can be improved by using rutile-type titanium oxide surface-treated with aluminum oxide, such as alumina. The content of rutile-type titanium oxide surface-treated with aluminum oxide in the total titanium oxide is, for example, 35 weight% or more, for example, 55 weight% or more, with an upper limit of 100 weight% or less; that is, the entire amount of titanium oxide may be rutile-type titanium oxide surface-treated with the aluminum oxide. Furthermore, since anatase-type titanium oxide has lower hardness than rutile-type titanium oxide, using anatase-type titanium oxide results in better moldability of the composition.

[0063] In the curable resin composition of the present invention, the amount of (B) white inorganic filler may be in the range of 20 to 60 weight%, for example, 30 to 60 weight%, or for example, 30 to 50 weight% with respect to the total resin composition. The content of (B) white inorganic filler may be calculated based on the solid content conversion standard. When the content of (B) white inorganic filler is within the above range, it is advantageous for high reflectivity; when it is less than the above range, the reflectivity decreases; and when it exceeds the above range, cracks may occur.

[0064] (B) Among the white inorganic fillers, the titanium oxide may have a sulfur concentration of 100 ppm or less, or 50 ppm or less. In addition, commercially available titanium oxide with a sulfur concentration of 100 ppm or less may be used, or commercially available titanium oxide with a sulfur concentration of 100 ppm or more may be blended after lowering the sulfur concentration by heat treatment, chemical treatment, or purification treatment such as washing or calcination. Here, the sulfur contained in the titanium oxide refers to all sulfur detected by analysis. This includes sulfur adsorbed on the titanium oxide and sulfur coated on the titanium oxide as impurities. In addition, the titanium oxide may have a sodium concentration of 100 ppm or less, or 50 ppm or less. A lower sodium concentration may be preferable. If the sodium concentration is too high, corrosion or oxidation may be accelerated when the copper substrate is exposed to moisture by sodium ions. For this reason, the concentration of sodium ions may be 100 ppm or less.

[0065] In addition, the curable resin composition of the present invention may contain titanium oxide with a sulfur concentration of 100 ppm or more, provided that it does not impair the effects of the present invention. Examples of titanium oxide with a sulfur concentration of 100 ppm or more include Ishihara Sangyo Co., Ltd. CR-58, CR-90, R-630, Sakai Kagaku Kogyo Co., Ltd. R-21.

[0066] In addition, rutile-type chlorinated titanium oxide such as T-550, T-580, R-630, R-820, CR-50, CR-60, R-90, CR-97 from Ishihara Sangyo Co., Ltd., or Ti PURE R-706, R-902+, R931 from DuPont, TR-600, TR-700, TR-840 from Fujichitan Kogyo Co., Ltd., and KR-270, KR-310, KR-380 from Chitan Kogyo Co., Ltd. can be used.

[0067] If the particle size of titanium oxide is too small, its fluidity deteriorates, and conversely, if it is too large, its insertability into small diameter substrates may deteriorate. Taking these factors into consideration, the median particle size of titanium oxide is in the range of 0.1 to 5 μm, for example, 0.1 to 1 μm, for example, 0.1 to 0.5 μm, and may be 0.36 μm. High reflectivity can be exhibited when the particle size of titanium oxide is within the above range. The above particle size was measured using a laser diffraction method.

[0068] (B) Among the white inorganic fillers, barium sulfate includes precipitated barium sulfate #100, precipitated barium sulfate #300, precipitated barium sulfate SS-50, BARIACE B-30, BARIACE B-31, BARIACE B-32, BARIACE B-33, BARIACE B-34, BARIFINE BF-1, BARIFINE BF-10, BARIFINE BF-20, BARIFINE BF-40 (manufactured by Sakai Kagaku Kogyo Co., Ltd.), W-1, W-6, W-10, C300 (manufactured by Takehara Kagaku Kogyo Co., Ltd.).

[0069] (B) Among the white inorganic fillers, silica is not particularly limited and can be obtained by methods known to a person skilled in the art. For example, it can be manufactured by burning silicon powder using the VMC (Vaporized Metal Combustion) method. The VMC method is a method of obtaining oxide particles by forming a chemical flame with a burner in an atmosphere containing oxygen, and then introducing a metal powder constituting part of the target oxide particles into the chemical flame in an amount sufficient to form a dust cloud, thereby causing knocking. Examples of commercially available silica include the SO series manufactured by Admatex Co., Ltd. and the HPS series manufactured by Doa Kosei Co., Ltd. (HPS-0500, HPS-1000, HPS3500, etc.).

[0070] [Body Pigment]

[0071] The extender pigment of the present invention refers to a pigment with a refractive index of 1.40 or higher, and may be, for example, silica such as amorphous silica, crystalline silica, fused silica, or spherical silica, talc, boehmite, hydrotalcite, slaked lime, calcium hydroxide, calcium carbonate, calcium sulfate, potassium carbonate, magnesium carbonate, clay, mica powder, aluminum oxide, aluminum hydroxide, barium sulfate, copper sulfide, alumina, zinc oxide, iron, zinc sulfide, zirconium oxide, chromium oxide, cadmium oxide, cadmium sulfide, titanium oxide, or copper oxide. Among these, talc, barium sulfate (BaSO4), silica, and calcium carbonate (CaCO3) may be used for the sake of dispersibility. By incorporating the extender pigment, heat resistance can be improved or deviation during application can be reduced.

[0072] The presence or absence of surface treatment of the extender pigment is not particularly limited, but surface treatment to improve dispersibility may be performed. By using a surface-treated extender pigment, aggregation can be suppressed. The method of surface treatment of the extender pigment is not particularly limited and any known or conventional method may be used, but it is preferable to treat the surface of the inorganic extender pigment with a surface treatment agent having a curable reactive group, for example, a coupling agent having a curable reactive group as an organic group.

[0073] The upper limit of the average particle size of the extender pigment may be, for example, 20 μm or less, 15 μm, or 13 μm. The lower limit of the average particle size of the extender pigment may be, for example, 0.01 μm, 0.1 μm, or 1 μm.

[0074] The average particle size of extender pigments refers to the average particle size (D) that includes not only the particle size of primary particles but also the particle size of secondary particles (aggregates). 50 ) and D measured by laser diffraction 50It is the value of. An example of a measuring device using the laser diffraction method is the Microtrac MT3300EXII manufactured by Microtrac Bell Co., Ltd. In addition, the maximum particle size (D 100 ) and particle size (D 10 ) can also be measured in the same way using the above device. In addition, the values ​​of each particle size of the above-described extender pigment refer to the values ​​measured by the extender pigment before adjusting (preliminary stirring, mixing) the curable resin composition as described above.

[0075] A curable resin composition according to one embodiment of the present invention may include two types of extender pigments with different particle sizes.

[0076] In one aspect of the present invention, a curable resin composition comprises (C) a first extender pigment and (D) a second extender pigment, wherein the average particle size of the first extender pigment is larger than the average particle size of the second extender pigment.

[0077] In one aspect of the present invention, the average particle size of the first extender pigment and the second extender pigment may be 1 to 13 μm.

[0078] In one aspect of the present invention, the average particle size of the first extender pigment may be 3 to 13 μm, 3 to 10 μm, or 3 to 7 μm.

[0079] In one aspect of the present invention, the average particle size of the second extender pigment may be 1 to 4 μm, 1 to 3 μm, or 1.5 to 2.5 μm.

[0080] The curable resin composition of the present invention can increase the surface roughness of the cured product formed by the curable resin composition by including the first extender pigment, and can increase the thixotropic index by including the second extender pigment. By including the first extender pigment and the second extender pigment, the mura phenomenon is improved, while excellent discoloration stability and / or reflectance characteristics can be exhibited.

[0081] In the curable resin composition of the present invention, the content of the first extender pigment may be 25% by weight or less based on the total weight of the resin composition. In the curable resin composition of the present invention, the content of the second extender pigment may be 6% by weight or less based on the total weight of the resin composition. By including the first extender pigment in the above-described content range, the curable resin composition of the present invention can suppress a decrease in reflectance, and by including the second extender pigment in the above-described content range, it can suppress a decrease in leveling.

[0082] In the curable resin composition of the present invention, the content of the first extender pigment may be greater than the content of the second extender pigment. By including the first extender pigment in a greater amount than the second extender pigment, the curable resin composition of the present invention can maximize mattification with a small amount of extender pigment. Since there is a limit to mattification when only the first extender pigment is used, the first extender pigment and the second extender pigment may be used together.

[0083] The sum of the content of the first extender pigment and the second extender pigment in the curable resin composition of the present invention may be 3 weight% or more, 5 weight% or more, 6 weight% or more, 6.5 weight% or more, 7 weight% or more, or 10 weight% or more with respect to the total composition.

[0084] The sum of the contents of the first extender pigment and the second extender pigment in the curable resin composition of the present invention may be 40% by weight or less, 35% by weight or less, 32% by weight or less, or 30% by weight or less with respect to the total composition.

[0085] The above composition includes a solid and a solvent. The content of the first extender pigment and the second extender pigment may be calculated based on the solid content conversion standard.

[0086] [(E) Photoinitiator]

[0087] A photoinitiator is intended to react a curable resin by exposure to light. Any known photoinitiator may be used. A single type of photoinitiator may be used alone, or two or more types may be used in combination.

[0088] Specifically, as photoinitiators, bis-acylphosphine oxides such as bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, and bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; Monoacylphosphine oxides such as 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphinate methyl ester, 2-methylbenzoyldiphenylphosphine oxide, pivaloylphenylphosphinate isopropyl ester, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and ethyl phenyl(2,4,6-trimethylbenzoyl)phosphinate; Hydroxyacetophenones such as 1-hydroxy-cyclohexylphenylketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one; benzoins such as benzoin, benzyl, benzoin methyl ether, benzoin ethyl ether, benzoin n-propyl ether, benzoin isopropyl ether, benzoin n-butyl ether, etc.; benzoin alkyl ethers; Benzophenones such as benzophenone, p-methylbenzophenone, mihiller ketone, methylbenzophenone, 4,4'-dichlorobenzophenone, 4,4'-bisdiethylaminobenzophenone;Acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1,2-(dimethylamino)-2-[(4-methylphenyl)methyl)-1-[4-(4-morpholinyl)phenyl]-1-butanone, N,N-dimethylaminoacetophenone; Thioxantones such as thioxantone, 2-ethylthioxantone, 2-isopropylthioxantone, 2,4-dimethylthioxantone, 2,4-diethylthioxantone, 2-chlorothioxantone, 2,4-diisopropylthioxantone; anthraquinones such as anthraquinone, chloroanthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-amylanthraquinone, 2-aminoanthraquinone; ketal compounds such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzoic acid esters such as ethyl-4-dimethylaminobenzoate, 2-(dimethylamino)ethyl benzoate, and p-dimethylbenzoate ethyl ester; Oxime esters such as 1,2-octanedione, 1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime), ethanolone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyloxime); titanocenes such as bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)phenyl)titanium, bis(cyclopentadienyl)-bis[2,6-difluoro-3-(2-(1-phil-1-yl)ethyl)phenyl]titanium, bis(2,6-difluoro-3-(1-hydropyrrole-1-yl)phenyl)titanocene; Examples include phenyl disulfide, 2-nitrofluorene, butyroine, anisophosphorus ethyl ether, azobisisobutyronitrile, tetramethylthiuram disulfide, etc.

[0089] Commercially available α-aminoacetophenone-based photoinitiators include Omnirad 907, 369, 369E, and 379 manufactured by IGM Resins. Additionally, commercially available acylphosphine oxide-based photoinitiators include Omnirad TPO, TPO-L, and 819 manufactured by IGM Resins. Commercially available oxime ester-based photoinitiators include Irgacure OXE01 and OXE02 manufactured by BASF Japan Co., Ltd., N-1919 manufactured by ADEKA Co., Ltd., ADEKA OXE01 and NCI-831, NCI-831E, and TR-PBG-304 manufactured by Changzhou Tronly New Electronic Materials Co., Ltd. Commercially available titanocene-based photoinitiators include Mosaphoto 533 manufactured by UFC Corporation.

[0090] In the curable resin composition of the present invention, the content of (E) a photoinitiator is 0.1 to 10 weight%, 0.1 to 5 weight%, or 1 to 5 weight% with respect to the total composition. The composition comprises a solid and a solvent. The content of (E) a photoinitiator may be calculated based on the conversion of the solid content.

[0091] When the content of the photoinitiator is 0.1% by weight or more, the photocurability of the curable resin composition improves, and film properties such as chemical resistance also improve. On the other hand, when it is 10% by weight or less, light absorption on the surface of the resist film (cured film) improves, making it difficult for deep curability to decrease.

[0092] A photoinitiator or sensitizer may be used in combination with the above-mentioned photoinitiator. Examples of photoinitiator or sensitizers include benzoin compounds, anthraquinone compounds, thioxantone compounds, ketal compounds, benzophenone compounds, tertiary amine compounds, and xantone compounds. In particular, it is preferable to use thioxantone compounds such as 2,4-dimethylthioxantone, 2,4-diethylthioxantone, 2-chlorothioxantone, 2-isopropylthioxantone, and 4-isopropylthioxantone. The inclusion of thioxantone compounds can improve deep curability. Although these compounds may be used as photoinitiators, it is preferable to use them in combination with a photoinitiator. Furthermore, one type of photoinitiator or sensitizer may be used alone, or two or more types may be used in combination.

[0093] In addition, since these photoinitiators, photoinitiation aids, and sensitizers absorb specific wavelengths, in some cases, their sensitivity is reduced, and they may function as ultraviolet absorbers. However, they are not used solely for the purpose of improving the sensitivity of the resin composition. If necessary, they can be made to absorb light of a specific wavelength to increase the photoresponsiveness of the surface, change the line shape and aperture of the resist pattern to a vertical, tapered, or inversely tapered shape, and also improve the precision of the line width or aperture diameter.

[0094] [Other optional components]

[0095] Various additives may be added to the curable resin composition of the present invention as optional components, as needed. Specifically, oxetane compounds, thermosetting catalysts, antioxidants, organic solvents, various other additives, or mixtures of two or more of these may be added. As optional components, one or more of the following materials may be included.

[0096] <Oxetane Compound>

[0097] Next, oxetane compounds are described. The following general formula (I)

[0098]

[0099] (R in the equation 1 Specific examples of oxetane compounds containing an oxetane ring represented by (which represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms) include 3-ethyl-3-hydroxymethyloxetane (Doa Kosei Co., Ltd., trade name OXT-101), 3-ethyl-3-(phenoxymethyl)oxetane (Doa Kosei Co., Ltd., trade name OXT-211), 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane (Doa Kosei Co., Ltd., trade name OXT-212), 1,4-bis{[(3-ethyl-3-oxetanyl)methoxy]methyl}benzene (Doa Kosei Co., Ltd., trade name OXT-121), and bis(3-ethyl-3-oxetanylmethyl)ether (Doa Kosei Co., Ltd., trade name Examples include OXT-221, etc. Additionally, phenol novolak-type oxetane compounds, etc., may be used. These oxetane compounds may be used in combination with the above-mentioned epoxy compounds or may be used alone.

[0100] Thermosetting Catalyst

[0101] In the composition of the present invention, at least one of a thermosetting agent and a curing catalyst may be further added as a thermosetting catalyst. For example, the thermosetting catalyst may not overlap with the components (A) to (E) described above.

[0102] The thermosetting agent may be, for example, a polyfunctional phenolic compound, polycarboxylic acid and its acid anhydrides, aliphatic or aromatic first or second amines, polyamide resin, isocyanate compound, polymercapto compound, etc. The curing agent may be, for example, a polyfunctional phenolic compound, polycarboxylic acid and its acid anhydrides, and excellent workability and insulation properties can be obtained by using such a curing agent. The polyfunctional phenolic compound is not particularly limited as long as it is a compound having two or more phenolic hydroxyl groups within one molecule, and may be, for example, a known or conventional one. For example, the polyfunctional phenolic compound may be a phenol novolak resin, a cresol novolak resin, bisphenol A, allylated bisphenol A, bisphenol F, a novolak resin of bisphenol A, or a vinylphenol copolymer resin. The polyfunctional phenolic compound may be, for example, bisphenol A, thereby increasing reactivity and heat resistance. Polyfunctional phenolic compounds can undergo addition reactions with at least one or both of epoxy compounds and oxetane compounds in the presence of a suitable curing catalyst. Polycarboxylic acids and their acid anhydrides may be, for example, compounds having two or more carboxyl groups within one molecule and their acid anhydrides, for example, copolymers of (meth)acrylic acid, copolymers of maleic anhydride, condensates of dibasic acids, etc. Commercially available products include BASF’s John Krill (product name), Sartomer’s SMA resin (product name), and Shin Nihon Rika Co., Ltd.’s polyazellaic anhydride, etc.

[0103] In addition, the curing catalyst may be a compound that can serve as a curing catalyst in the reaction between a thermosetting resin, such as an epoxy compound and an oxetane compound, and a curing agent, or a compound that serves as a polymerization catalyst when a curing agent is not used. Specifically, the curing catalyst may be, for example, a tertiary amine, a tertiary amine salt, a quaternary ammonium salt, a tertiary phosphine, a crown ether compound, and a phosphonium ylide, and among these, it may be used individually or in combination of two or more types.

[0104] For example, imidazoles such as trade names 2E4MZ, C11Z, C17Z, 2PZ, imidazole AZINE compounds such as trade names 2MZ-A, 2E4MZ-A, isocyanurates of imidazoles such as trade names 2MZ-OK, 2PZ-OK, imidazole hydroxymethyl bodies such as trade names 2PHZ, 2P4MHZ, etc. (Trade name: Shikoku Kasei Kogyo Co., Ltd.), dicyandiamide and its derivatives, melamine and its derivatives, diaminomareonitrile and its derivatives, amines such as diethylenetriamine, triethylenetetramine, tetraethylenepentamine, bis(hexamethylene)triamine, triethanolamine, diaminodiphenylmethane, 1,8-diazabicyclo[5,4,0]undecen-7 (Trade name DBU, San Apro Co., Ltd.), It may be 3,9-bis(3-aminopropyl)-2,4,8,10-tetraoxaspiro[5,5]undecane (trade name ATU, Ajinomoto Co., Ltd.) or organic phosphine compounds such as triphenylphosphine, tricyclohexylphosphine, tributylphosphine, methyldiphenylphosphine, etc.

[0105] In the curable resin composition of the present invention, the curing catalyst may be an amine-based, phosphine-based, or imidazole-based curing catalyst, and for example, may be a melamine-based amine curing catalyst. The amount of the curing catalyst may be 0.1 to 10 weight%, 0.1 to 5 weight%, or 0.1 to 3 weight% based on the total composition.

[0106] When the content of the above curing catalyst is within the above range, the coating film is sufficiently cured, resulting in excellent adhesion, pencil hardness, and heat resistance, and the curing time can be appropriately managed while preventing a decrease in formability.

[0107] Antioxidants

[0108] The curable resin composition of the present invention may also contain an antioxidant. By including an antioxidant, not only can the effect of preventing oxidative degradation of the curable resin and suppressing discoloration be obtained, but also the effect of improving heat resistance and achieving good resolution (reproducibility of line width) can be obtained. That is, depending on the type of white coloring agent, resolution may be deteriorated by reflecting and absorbing light, but by including an antioxidant, good resolution can be obtained regardless of the type of white coloring agent. The antioxidant may be a radical scavenger that neutralizes generated radicals, or a peroxide decomposition inhibitor that decomposes generated peroxides into harmless substances and prevents the generation of new radicals, and may be a single type or a combination of two or more types.

[0109] Antioxidants that act as radical scavengers include, for example, phenolic compounds such as hydroquinone, 4-t-butylcatechol, 2-t-butylhydroquinone, hydroquinone monomethyl ether, 2,6-di-t-butyl-p-cresol, 2,2-methylene-bis(4-methyl-6-t-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, 1,3,5-tris(3',5'-di-t-butyl-4-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione, quinone compounds such as menaquinone and benzoquinone, It may be an amine compound such as bis(2,2,6,6-tetramethyl-4-piperidyl)-sebacate and phenothiazine. As for commercially available products, IRGANOX 1010 (BASF Japan Co., Ltd., trade name) may be used.

[0110] In addition, examples of antioxidants that act as peroxide decomposition agents include phosphorus-based compounds such as triphenylphosphite, sulfur-based compounds such as pentaerythritol tetralaurylthiopropionate, dilaurylthiodipropionate, and distearyl-3,3'-thiodipropionate.

[0111] For example, the antioxidant may be a phenolic compound, and when used, it is possible to achieve a discoloration inhibition effect, improved heat resistance, and better resolution.

[0112] In addition, antioxidants, such as phenolic antioxidants, can be used in combination with heat stabilizers. When used in combination, even better effects can be achieved.

[0113] The heat stabilizer may be, for example, a phosphorus-based, hydroxylamine-based, or sulfur-based heat stabilizer. The above heat stabilizer may be a single type or a combination of two or more types.

[0114] For example, the antioxidant may be a hydroxylamine-based antioxidant and a sulfur-based antioxidant, or a phenol-based antioxidant. When a phenol-based antioxidant is used, the amount of the antioxidant may be 0.01 to 5 weight% or 0.03 to 3 weight% with respect to the total composition. By making the amount of the antioxidant 0.01 to 1 weight% or more, the effect of adding the antioxidant can be reliably obtained, and if it is 1 weight% or less, good alkaline properties can be obtained without inhibiting the photoreaction, and good tack-free drying properties and coating film properties can also be ensured.

[0115] Organic solvents

[0116] The curable resin composition of the present invention may include an organic solvent for purposes such as manufacturing the composition or adjusting viscosity when applying it to a substrate or base. As the organic solvent, known and commonly used organic solvents may be used, such as esters; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, and solvent naphtha. These organic solvents may be used alone or in combination of two or more types.

[0117] Other Additives

[0118] In addition, other additives known and commonly used in the field of electronic materials may be incorporated into the curable resin composition of the present invention. Other additives may include thermal polymerization inhibitors, ultraviolet absorbers, plasticizers, flame retardants, antistatic agents, anti-aging agents, antibacterial and antifouling agents, defoaming agents, leveling agents, thickeners, fluidity additives, adhesion promoters, thixotropic promoters, photoinitiators, sensitizers, curing accelerators, release agents, surface treatment agents, dispersants, dispersion promoters, surface modifiers, stabilizers, diluents, etc.

[0119] [Dry film and method of manufacturing the same]

[0120] The curable resin composition of the present invention may be in the form of a dry film comprising a support (carrier) film and a resin layer formed on the support film, the resin layer comprising a dry film of the curable resin composition. When forming the dry film, first, the composition of the present invention is diluted with an organic solvent to adjust the viscosity to an appropriate level, and then applied to the support film in a uniform thickness, for example, in the range of 40 to 60 μm, by means of a comma coater, blade coater, lip coater, rod coater, squeeze coater, reverse coater, transfer roll coater, gravure coater, micro gravure coater, spray coater, etc.

[0121] After that, a dry film can be formed by drying the applied composition at a temperature typically in the range of 40 to 120°C for 1 to 30 minutes to form a resin layer consisting of a dried film.

[0122] There are no specific limitations on the thickness of the coating film, but generally, the thickness after drying can be 10 to 150 μm, 10 to 80 μm, or 10 to 60 μm.

[0123] As a support film, a plastic film is used, and for example, a polyester film such as polyethylene terephthalate (PET), a polyimide film, a polyamideimide film, a polypropylene film, a polystyrene film, etc., can be used, and for example, it can be polyethylene terephthalate. The thickness of the support film is not particularly limited, but can generally be appropriately selected in the range of 10 to 150 μm. It can also be applied to a metal foil such as copper foil or aluminum foil. In addition, the support film used can be subjected to a peeling treatment such as acrylic or silicone.

[0124] After forming a resin layer consisting of a dried film of the curable resin composition of the present invention on a support film, it is preferable to laminate a peelable protective (cover) film on the surface of the resin layer for purposes such as preventing dust from adhering to the surface of the resin layer. Examples of peelable protective films may be used, such as polyethylene film, polytetrafluoroethylene film, polypropylene film, or surface-treated paper, and it is sufficient that the adhesion between the resin layer and the protective film is smaller than the adhesion between the resin layer and the support film when the protective film is peeled off.

[0125] The thickness of the protective film is not specifically limited, but can be, for example, 10 μm to 150 μm.

[0126] Since the dry film of the present invention is white, it can be used to reflect light generated from a light-emitting diode (LED) or an electroluminescent (EL) used as a light source in backlights of liquid crystal displays such as lighting fixtures, portable terminals, notebook computers, tablet PCs, monitors, smartphones, personal computers, and televisions. The dry film of the present invention can be applied to LEDs and light-emitting PCBs, etc.

[0127] To produce a cured film on a printed circuit board using a dry film, a protective film is peeled off from the dry film, and the exposed resin layer of the dry film is overlapped onto a circuit-formed substrate and attached using a laminator or the like to form a resin layer on the circuit-formed substrate. Subsequently, a cured film can be formed by exposing, developing, and heating the formed resin layer and then curing it. The protective film can be peeled off at any stage before or after exposure.

[0128] [Curing material and method of manufacturing the same]

[0129] The cured product of the present invention may be formed by curing the resin layer of the curable resin composition of the present invention or the dry film of the present invention.

[0130] The cured product of the present invention can be suitably used for printed circuit boards and electronic components, etc. The cured product of the present invention may exhibit excellent dielectric properties, including high crack resistance, high resolution, low dielectric constant, and low dielectric loss tangent. In addition, the cured product of the present invention may also exhibit excellent heat resistance and a low coefficient of linear expansion.

[0131] For example, the cured product of the present invention may be a solder resist.

[0132] The above solder resist can be manufactured by applying the curable resin composition of the present invention onto a substrate to form a resin layer, then selectively exposing it to an active energy line through a photomask forming a predetermined pattern, and developing the unexposed portion with a dilute alkaline aqueous solution (e.g., 0.3 to 3 wt% sodium carbonate aqueous solution) to form a pattern. Alternatively, in the case of a dry film, a patterned solder resist can be formed on a substrate by peeling off the support film of the dry film after exposure and then performing development. Additionally, as long as the properties are not compromised, the support film can be peeled off from the dry film before exposure to expose and develop the exposed resin layer.

[0133] For example, the above-mentioned cured product may have an average surface roughness (Ra) of 0.2 or higher. That is, the cured product formed by the curable resin composition of the present invention has an average surface roughness of a certain range or higher, thereby exhibiting low gloss, excellent discoloration stability, and reflectance characteristics without any additional processing.

[0134] [Printed circuit board and method of manufacturing the same]

[0135] The printed circuit board of the present invention may include a cured film formed by curing a curable resin composition of the present invention or a resin layer of a dry film of the present invention.

[0136] The printed circuit board of the present invention may include a cured product obtained from the resin layer of the curable resin composition or dry film of the present invention. For example, a method for manufacturing the printed circuit board of the present invention may form a tacky-free resin layer by applying the curable resin composition of the present invention onto a substrate by a method such as dip coating, flow coating, roll coating, bar coater, screen printing, or curtain coating, after adjusting the viscosity suitable for the application method using the organic solvent of the present invention, and then evaporating and drying (pre-drying) the organic solvent contained in the composition at a temperature of 60 to 100°C. In addition, in the case of a dry film, the resin layer may be formed on the substrate by bonding it to the substrate using a laminator or the like so that the resin layer comes into contact with the substrate, and then peeling off the support film.

[0137] The above description includes not only printed circuit boards formed with circuits such as copper and flexible printed circuit boards, but also materials such as paper phenol, paper epoxy, glass fiber epoxy, glass polyimide, glass fiber / epoxy, glass fiber / paper epoxy, synthetic fiber epoxy, fluoropolymer, polyethylene, polyphenylene ether, polyphenylene oxide cyanate, etc., for copper clad laminates for high-frequency circuits, such as FR-4 substrates, copper clad laminates of all grades (FR-4, etc.), other metal substrates, polyimide films, polyethylene terephthalate films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, wafer substrates, etc.

[0138] As a method for laminating a dry film onto a substrate, the process can be carried out by applying pressure and heating using a vacuum laminator, etc. By using such a vacuum laminator, even if the surface of the circuit board is uneven when using a circuit-formed substrate, the dry film adheres to the circuit board, so there is no incorporation of bubbles, and the relief of concave parts on the surface of the substrate can be improved. The pressure condition may be about 0.1 to 2.0 MPa, and the temperature condition may be 40 to 120°C.

[0139] In addition, a cured film with excellent adhesion, hardness, and various other properties can be formed by i) heat curing (e.g., 100 to 220°C) after irradiating an active energy ray, ii) irradiating an active energy ray after heat curing, iii) irradiating an active energy ray only, or iv) heat curing only for final curing.

[0140] The cured product of the present invention can form a cured film with excellent general characteristics, such as high reflectivity, excellent yellowing resistance, and excellent crack resistance, by heating and curing it at a temperature of, for example, 100 to 220°C.

[0141] The exposure device used for the above active energy beam irradiation may be a device equipped with a high-pressure mercury lamp, ultra-high-pressure mercury lamp, metal halide lamp, mercury short arc lamp, etc., and irradiating ultraviolet (UV) light in the range of 350 to 450 nm, and may also be a direct imaging device (e.g., a laser direct imaging device that draws an image directly with a laser based on CAD data from a computer). The laser light source of the direct imaging device may have a maximum wavelength in the range of 350 to 450 nm. The exposure for image formation varies depending on the thickness, but is generally 10 to 1000 mJ / cm² 2 It can be, or 20–800 mJ / cm² 2 It could be.

[0142] The above development method may be a method by dipping, showering, spraying, brushing, etc., and as the developer, an alkaline aqueous solution such as potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, amines, etc. may be used.

[0143] The printed circuit board of the present invention may include a dry film comprising one or more layers formed from the curable resin composition.

[0144] When forming a printed circuit board, a dry film can be placed on a test board and transferred onto the test board by vacuum lamination.

[0145] Subsequently, the support film is peeled off, and the substrate onto which the dry film has been transferred can be UV exposed using an exposure device. When exposed in this manner, the exposed area (the irradiated part) can be cured. After exposure, the substrate is cooled at room temperature and then placed in a developer to develop the unexposed area using an alkaline aqueous solution, thereby completing the formation of the resist pattern. The substrate with the pattern formed through development is post-cured in an oven to complete the substrate fabrication. After post-curing, a reflow process is performed, followed by a chip mounting process. Subsequently, a process of fabricating a silicone encapsulant on the cured product of the curable resin layer is carried out, and an encapsulation process can be performed.

[0146] <Example>

[0147] The present invention will be explained in detail below using examples. The present invention is not limited to the following examples.

[0148] Preparation of a curable resin composition

[0149] A curable resin composition was prepared by placing the raw materials into a container and stirring. The content of each component is as listed in Table 1 below.

[0150] [Table 1] Content of each component of the curable resin composition (Unit: weight% relative to the total composition)

[0151]

[0152] The details of each component shown in Table 1 above are as follows.

[0153] Curable resin A: Uses a mixture of the following components (1) and (2) in a 2:1 ratio.

[0154] (1) EPICLON R-2000K (DIC), ACRYLATE RESIN on CRESOL NOVOLAC framework,

[0155] (2) YD-128W (Kukdo Chemical), BPA Epoxy resin

[0156] Curable resin B: Uses the following components (1) to (3) mixed in a 1:1:1 ratio.

[0157] (1) CYCLOMER-P (ACA)Z254F (DIC), ACRYLATE RESIN of CYCLOMER skeleton,

[0158] (2) UE-6500 (DIC), acrylate copolymer,

[0159] (3) YD-128W (Kukdo Chemical), BPA Epoxy resin

[0160] Antifoaming agent: (1) KS-66 (Shin-etsu chemical)

[0161] Dispersant: (1) BYK-111 (BYK)

[0162] Antioxidant: ADK STAB AO-60 (ADEKA)

[0163] Leveling agent: (1) BYK-1791 (BYK)

[0164] Flow additives: (1) BYK-405(BYK) (2) BYK-606(BYK)

[0165] Diluent: (1) DOWANOL DPM (DOW)

[0166] Thermosetting agent: (1) KH-1600 (NINGXIA DARONG CHEMICALS)

[0167] (2) MELAMIN FUNSAI (JingShan Ink Material Manufacturing (Huai))

[0168] Photoinitiator: (1) TPO-L (IGM Resins) (2) Mosaphoto 533 (UFC Corporation)

[0169] Titanium oxide: TIPAQUE CR-90, manufactured by ISHIHARA Industry (Average particle size: 0.25 µm)

[0170] Extender Pigment A: Talc (KHP-25, manufactured by Koch) (Average particle size: 4.75 µm)

[0171] Extender Pigment B: Fumed Silica (NIPSIL L-300, manufactured by Tosoh) (Average particle size: 1.5~2.5 µm)

[0172] Barium Sulfate (BaSO4): BARIACE B-33, manufactured by Sakai Kagaku Kogyo Co., Ltd. (Average particle size: 300 nm)

[0173] Alumina (Al2O3): DAW-20, manufactured by Denka Company (Average particle size: 23.8 µm)

[0174] Preparation of a dry film of a curable resin composition

[0175] Using a comma coater in a dust-free room, (1) the compositions of each example and comparative example were applied to a support film (PET film) (Toray XD-500P, film thickness: 25㎛) with a uniform thickness (50㎛). (2) The applied compositions were dried in four temperature chambers ranging from 40 to 120℃ (Chamber 1: 60℃, Chamber 2: 80℃, Chamber 3: 100℃, Chamber 4: 100℃). (3) A dry film was prepared by laminating the appropriately dried coating film on the support film with a protective film (Polypropylene, PP film). At this time, the thickness of the dried coating film was set to be in the range of 60㎛.

[0176] Reflectance measurement

[0177] The dry films prepared in Examples 1 to 9 and Comparative Examples 1 to 4 were laminated and exposed to light at 600 mJ / cm² using an integrating photometer. The film was then developed for 60 seconds using a 1% Na2CO3 aqueous solution at 30°C under a spray pressure of 0.2 MPa, and cured in a 150°C oven for 60 minutes to obtain a substrate. The obtained substrate was placed in a chamber (HIFLEX, Temperature and humidity chamber, ETAC) under conditions of 85°C and 85% humidity and left for 1000 hours. For the substrate left in the HS chamber for 1000 hours, the average reflectance was measured using a spectrophotometer (CM-700d, Konica Minolta Japan Co., Ltd.).

[0178] Reflectance was evaluated based on the following criteria.

[0179] ○: Over 87%

[0180] △: 86% or more and 87% or less

[0181] X: Less than 86%

[0182] Discoloration stability

[0183] For the substrate fabricated using the same method as the substrate fabricated in the reflectance measurement, ΔE was measured using a spectrophotometer (CM-700d, Konica Minolta Japan Co., Ltd.) * The ab value was measured and evaluated according to the following criteria.

[0184] ○: Color difference ΔE * ab value less than 1

[0185] △: Color difference ΔE * ab value 1 or greater, 2 or less

[0186] X: Color difference ΔE * ab value exceeds 2

[0187] In this specification, the statement that the composition has excellent discoloration stability means that the color difference is not significant, and thus the composition can effectively prevent discoloration.

[0188] Crack resistance evaluation (Erichsen test)

[0189] For the coating surface of a substrate fabricated using the same method as the substrate fabricated for reflectance measurement, the Ericsson Index (EI) value was measured according to the international standard test ISO 20482:2003. Crack resistance was evaluated based on the following criteria.

[0190] ○: EI value greater than 0.6

[0191] △: EI value 0.2 or higher, 0.6 or lower

[0192] X: EI value less than 0.2

[0193] Gloss evaluation

[0194] For the coating surface of a substrate prepared using the same method as the substrate prepared for reflectance measurement, the gloss at an angle of 60° was measured using a gloss colorimeter (BYK E-4430). The gloss was evaluated according to the following criteria.

[0195] ○: Less than 35GU

[0196] △: 35 to 80GU

[0197] X: Exceeds 80GU

[0198] Average surface roughness (Ra) measurement

[0199] The average surface roughness value was measured using a contact roughness meter on the coating surface of a substrate prepared using the same method as the substrate prepared for the reflectance measurement.

[0200] MURA evaluation

[0201] The occurrence of mura was observed visually on the surface of the coating film of a substrate prepared using the same method as the substrate prepared for reflectance measurement. The mura evaluation criteria were evaluated using numbers from 1 to 6 as shown in Fig. 1, where 1 means that no mura was observed, and the higher the number, the more mura was observed.

[0202] Evaluation of leveling performance

[0203] The smoothness of the coating surface of the substrate fabricated using the same method as the substrate fabricated for the reflectance measurement was visually inspected. The evaluation criteria are as follows.

[0204] ○: Excellent smoothness with almost no variation observed on the coating surface.

[0205] △: Some variation in the surface of the coating is observed, but it is at a level that is not problematic.

[0206] X: There are many areas where deviations in the coating surface are observed.

[0207] [Table 2]

[0208]

[0209] Referring to Table 2, Comparative Examples 1 and 2 used only one type of extender pigment, which shows that there is no improvement effect when using only extender pigment A or B without using two types of extender pigments with different average particle sizes.

[0210] When comparing Example 1 and Comparative Example 4, it can be seen that when the first extender pigment is used in excess (when the content of the first extender pigment exceeds 25% by weight based on the total weight of the resin composition), the leveling is poor, the crack resistance is poor, and the reflectivity is insufficient.

[0211] Example 5 ensures improved mura, but uses a resin applied to colored photo solder resist (PSR), so reflectance and discoloration stability are not ensured, and therefore it is not suitable as a solder resist for reflectors used in displays, etc.

[0212] Example 6 showed effectiveness in discoloration stability, crack resistance, gloss, and leveling, but because a filler with an average particle size of 2 μm or less was used as the second extender pigment, the shielding power was lowered, the reflectance was lowered, and the Ra value was lowered, resulting in severe mura. Example 7 showed effectiveness in discoloration stability, crack resistance, gloss, and improvement of mura, but because a filler with an average particle size of 12 μm or more was used as the first extender pigment, the Ra value increased, the reflectance decreased due to diffuse reflection, and it can be seen that the leveling deteriorated.

[0213] Comparative Example 3, which contains no extender pigment at all, shows higher gloss and more severe mura when compared to Examples 1 to 7 and 9, which contain a sufficient amount of extender pigment. Example 8 also shows effects in reflectance, discoloration stability, and crack resistance, but even though it contains extender pigment, the total amount of extender pigment is low, resulting in higher gloss and more severe mura. Example 9 shows that compared to Example 3, the content range of the second extender pigment exceeds 6 weight%, which fails to suppress the decrease in leveling and causes mura.

Claims

Claim 1 A curable white resin composition comprising (A) a curable resin, (B) a white inorganic filler, (C) a first extender pigment, (D) a second extender pigment, and (E) a photoinitiator, wherein the average particle size of the first extender pigment is larger than the average particle size of the second extender pigment, the average particle size of the first extender pigment is 3 to 13 μm, the average particle size of the second extender pigment is 1 to 4 μm, the content of the first extender pigment is 25 wt% or less based on the total weight of the resin composition, and the first extender pigment and the second extender pigment are independently selected from talc, barium sulfate (BaSO4), silica, and calcium carbonate (CaCO3), and the average surface roughness (Ra) of the cured product obtained by curing the curable white resin composition is 0.2 μm or more. Claim 2 A curable white resin composition according to claim 1, wherein the (B) white inorganic filler is titanium oxide, zinc oxide, basic carbonate, basic sulfate, sulfate, zinc sulfide, antimony oxide, aluminum hydroxide, silica, barium sulfate, or a combination thereof. Claim 3 A curable white resin composition according to claim 1, wherein the content of the first extender pigment is greater than the content of the second extender pigment. Claim 4 A curable white resin composition according to claim 1, wherein the content of the second extender pigment is 6% by weight or less based on the total weight of the resin composition. Claim 5 A curable white resin composition according to claim 1, wherein the sum of the contents of the first extender pigment and the second extender pigment is 6% by weight or more based on the total weight of the resin composition. Claim 6 A curable white resin composition for forming a solder resist, according to claim 1. Claim 7 A dry film comprising a support film and a resin layer formed on the support film, the resin layer being a dry film of a curable white resin composition according to any one of claims 1 to 6. Claim 8 A cured product obtained by curing the resin layer of a dry film according to paragraph 7. Claim 9 A printed circuit board containing a cured material according to paragraph 8. Claim 10 A cured product obtained by curing a curable resin composition according to any one of claims 1 to 6. Claim 11 A printed circuit board containing a cured material according to Clause 10. Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete Claim 16 delete Claim 17 delete

Citation Information

Patent Citations

  • Photocurable resin composition, dry film, cured material, and printed wiring board

    JP2012215716A

  • Curable resin composition, and dry film and printed wiring board using the same

    JP2012215718A

  • Resin composition for laminated electronic components, dry film, cured product, laminated electronic components and printed wiring boards

    KR1020200124700A

  • White solder resist composition, dry film, printed wiring board and method for producing them

    KR1020220086524A

  • Photocurable resin composition, dry film, cured product, and printed wiring board

    KR1020140018280A